Persepsi Sosial pada Hubungan Tanpa Status di Kalangan Remaja - Handayani, Lilis; Lestari, Dwi Ardisa; Nirmala, Prita; Sijabat, Rauly (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The phenomenon known as a "situation ship" has become increasingly common among teenagers due to changes in social values, culture, and the influence of social media. Situation ships offer freedom without commitment but often lead to emotional impacts such as confusion and stress. This study aims to explore the reasons behind teenage involvement in situation ships, their social perceptions, and the role of social media in shaping these relationship dynamics. Using qualitative methods with in-depth interviews from three teens aged between 15 and 24 years old, the research findings indicate that situation ships are attractive because of their flexibility but also carry significant emotional risks. Social media reinforces the normalization of this type of relationship among young people. The study recommends clear communication and increased literacy about relationships for adolescents.